The Use of Wind Energy to Reduce Energy Consumption of Shrimp Farm Aerators: A Case Study of Thailand - Worasinchai, Supakit; Limthongkul, Pimpa; Suwannakij, Kiatkong; Powsakul, Wanita (Asian Health, Science and Technology Reports, 2017)
The level of the dissolved oxygen in the grow-out water is one of the most important parameters that govern the quality of shrimp production. The generation of dissolved oxygen in intensive farms relies heavily on mechanical aerators which consume a large amount of energy. Reduction of this energy consumption could be beneficial for farm owners as it reduces the operational cost of the farm. This article presents a study of using wind power to reduce the operational cost of the paddle-wheel aerators. A hybrid system, which combines the wind power source to the motor-based electric system was designed and evaluated under Thai wind conditions. The study showed that the investment has a long payback period of around 18 years and this is mainly because of the high energy cost of the wind turbine. Results also showed that reduction of this cost and the improvement of the wind turbine performance can be implemented in parallel to improve the cost-effectiveness of the system. Therefore, the use of wind power to supply power to the aerator system will not be cost-effective until the energy cost of the wind turbine has been improved.